Talking about the problem: a content analysis of pre-search interviews - T.D. Wilson (Information Research: An International Electronic Journal)
The pilot study reported here applies content analysis techniques to twenty interviews carried out in preparation for mediated searches as part of the 'Uncertainty in Information Seeking' project. The tools used in the analysis (Atlas.ti and TEXTStat) are described and their contribution assessed. TEXTStat, a free program, was used to produce frequency counts of the words used in the interview and to examine the context of those words. Atlas.ti was used to assign codes to the interview transcripts and to model the relationships among these codes. The mode of analysis of the cases is qualitative and interpretative and the results reveal the complexity of the information problems, the variety of motivations for undertaking a mediated search, the difficulties of expressing the search concepts, and the relationship between the need for a search and previous information seeking behaviour.